FEEDING HABIT OF FRESHWATER LOBSTER (Cherax quadricarinatus) IN THE RIAU UNIVERSITY AQUATIC ECOSYSTEM - Yogi Pramana Putra; Windarti '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Streams, dam and pool around the University of Riau is inhabited by many types of aquatic organisms, including freshwater loster (Cherax quadricarinatus). Freshwater lobster (Cherax quadricarinatus) is an alien species originated from Austalia. So far, the information obtained is only limited to type identification, while other information on the lobster is not yet known. To understand the feeding habit of freshwater lobster in the aquatic ecosystem, a research has been conducted in December-January 2017. There were three sampling areas, namely an earthen pool around the Rektorat Building (Station 1), the dam (Station 2) and the stream in the back of Marine Science Building (Station 3). Samplings were conducted everyday for a one month period. Lobster was captured using a scoop net and pit traps. Stomach content analysis was performed in the laboratory. Total number of lobster sampled was 40. Results shown that the main food of the lobster is detritus (IP>40%), the complementary food is fish remains, plant and phytoplankton (IP 4-40%).Keyword : Cherax quadricarinatus, Lobster, Index of preponderance, Stream, dam